Experiments and thermodynamic models for ternary liquid–liquid equilibrium systems of water + tetrahydrofurfuryl alcohol + solvents at different temperatures. (April 2022) - Han, Mai; Lin, Song; Xu, Mingyi; Jiang, Yueyang; Yin, Qingqing; Pang, Yufan; Song, Yujian; Li, Qingsong
Highlights: Supplements the relevant data of the THFA + water system to provide a data basis for industrial separation of THFA. The binary interaction parameter values were obtained by UNIQUAC and NRTL models. The calculated solubility data agree well with the experimental values. The fitting parameters were inspected by the GUI-MATLAB tool. Abstract: In order to extract and refine tetrahydrofurfuryl alcohol (THFA) from water, this work obtained the liquid–liquid equilibrium (LLE) data of THFA in the aqueous solution using 4-Methyl-2-pentanone (MIBK) and 4-Methyl-2-pentanol (MIBC) at 303.2 K, 313.2 K, and 323.2 K under 101.3 kPa. The distribution coefficient ( D ) and selectivity coefficient ( S ) were used to evaluate the effect of extracting THFA from an aqueous solution, and it is found that both two solvents are excellent for the extraction of THFA. The Othmer-Tobias and Hand equations were used to verify the reliability of the LLE data with the linear coefficient was greater than 0.99%. The NRTL and UNIQUAC models successfully correlated the experimental data with the RMSD% values less than 0.57% and 0.56%, respectively. The GUI-MATLAB tool was used to verify the excellent reliability of the regression parameters.